Practical stress analysis in engineering design - Huston, Ronald L., 1937- (Mechanical engineering (Taylor & Francis), 2009)
This third edition provides coverage of new topics including contact stress analysis, singularity functions, gear stresses, fasteners, shafts, and shaft stresses. It introduces finite and boundary element methods and also features worked examples, problems, and a section on the finite difference method and applications.